Evaluation of a GIS-based watershed modeling approach for sediment transport - Nangia, Vinay; Wymar, Paul; Klang, James (International Journal of Agricultural and Biological Engineering, 2010)
In order to improve water quality and restore impaired watersheds, managers need to make decisions using data that are able to gather. Data collection can be expensive, tedious and time consuming. Not all watershed managers have sufficient budgets to undertake such exercises. In such situations using modeling approach makes sense. The Sediment Nutrient Assessment Program (SNAP) is a functionally distributed model. It uses Geographic Information System (GIS)-based methodology employing commonly used Revised Universal Soil Loss Equation (RUSLE) to estimate the amount of erosion that can occur in the study area and Flux model for estimating the sediment transport. By adopting this methodology a modeler can estimate fractions of sediment contributions from the three landforms (upland, surface tiled, riparian). An intermediate result is mapping of areas producing erosion at rates above, below and equal to tolerable rates for each soil type. The model works best on smaller watersheds where staff have time and resources to inventory water quality. A good understanding of the watershed is needed to validate the model outputs. The model implementation is relatively cheap, cost effective and easy. Existing data and freely available information in the public domain are used for computations. It takes a multifaceted and holistic approach by integrating current, localized research literature, field surveys, water quality data, and GIS into one tool for refining watershed management decisions. The SNAP model serves as a first stage of analyzing as to how bad the sedimentation problem is with limited resources. Keywords: sediment transport, watershed, GIS, soil erosion, RUSLE, modeling DOI: 10.3965/j.issn.1934-6344.2010.03.043-053 Citation: Vinay Nangia, Paul Wymar, James Klang. Evaluation of a GIS-based watershed modeling approach for sediment transport. Int J Agric & Biol Eng, 2010; 3(3): 43<span style="font-size: 9pt; line-height: 140%; font-family: